DEVELOPMENT OF ATTRACTING FINANCIAL RESOURCES FROM THE CAPITAL MARKET TO THE CORPORATE SECTOR - Khasanov Khairulla Nasrullaevich (Scholar Express Journals, 2023)
This article covers the development of attracting financial resources from the capital market to the corporate sector. It is known from the research results that the methodology for evaluating the effectiveness of the middle tranche should be based on the following methodological guidelines. This efficiency assessment should also be carried out on the basis of the comparison of the forecast values of the selected efficiency and actual costs and the obtained results in the evaluation of the efficiency of the corporate sector in servicing the financial resources involved in the project phase
Keywords: Development of attracting financial resources,; capital market; corporate sector